Anti-tumor necrosis factor-α therapy may not be safe during pregnancy in women with inflammatory bowel disease: an updated meta-analysis and systematic review - Wei Huang; Xinxing Zhang; Li Zhang; Xiaosong Dai; Heping Chen; Qin Xie (BMC Pregnancy and Childbirth, 2024)
Abstract Background Inflammatory Bowel Disease (IBD) affects reproductive-aged women. Active disease can lead to decreased fertility. Although the vast majority of international guidelines recommend for the continuation of anti-TNF-α during pregnancy, recent studies have raised concerns about the safety of anti-tumor necrosis factor-α (TNF-α) therapy during pregnancy, both for patients and for physicians. Methods Studies that evaluate the safety of anti-TNF-α therapy in pregnant women with IBD were identified using bibliographical searches. An updated meta-analysis was performed for pregnancy outcomes, such as live birth, abortion, still birth, preterm birth, low birth weight, congenital abnormalities, and neonatal infection. Odds ratio (OR) with 95% confidence interval (CI) are reported. Data on disease activity, timing of anti-TNF-α therapy were collected for further analysis. Results Overall, 11 studies were screened from on-line databases and international meeting abstracts. An increased risk of abortion (OR, 1.33; 95% CI, 1.02–1.74; P = 0.04) and preterm birth (OR, 1.16; 95% CI, 1.05–1.28; P = 0.004), and a decreased risk of live birth (OR, 0.83; 95% CI, 0.74–0.94; P = 0.002]) were found in the anti-TNF-α therapy group compared with the control group (no use of anti-TNF-α therapy). The subgroup analyses based on the disease activity showed there is no significant association between the use of anti-TNF-α therapy during pregnancy on adverse pregnancy outcomes of abortion, preterm birth, and live birth. The rates of still birth, low birth weight, and congenital abnormalities in the anti-TNF-α therapy group were not significantly different from those in the control group. Conclusions Anti-TNF-α therapy does not increase the risks of still birth, low birth weight, and congenital abnormalities; however it may be assicated with increased risks of abortion and preterm birth, which are accompanied by a lower rate of live birth. Although these findings may be confounding by potential disease activity, they offer some opposite viewpoints with biologic agent use. Therefore, more studies are required to further confirm the safety of anti-TNF-α therapy in pregnancy with IBD.